Padrões de resposta do pessegueiro cv. Maciel a diferentes níveis de déficit hídrico. - Simões, Fabiano (2007)
The peach fruit production for processing in Southern of Rio Grande do Sul responds for 90% of the national production. The droughts probabilities in the summer in this region have coincided with the critical periods to water lack of the culture. Therefore, it becomes necessary a supplementation by irrigation aiming high quality for both culture and fruit production. The objective of this work was to assess responses standard of the peach tree cv. Maciel to different levels of water stress. It was carried out two experiments using trees cultivated into weight lysimeter at Embrapa Clima Temperado, Pelotas/RS, during 2005/06 and 2006/07 crops. The irrigation levels were based on plant transpiration. Thus, the levels in the fist experiment were: N1 100% of transpirated water replacement, N2 80%, N3 60 % and N4 40%. In the second experiment the values were 100%, 75%, 50% and 25% respectively. It was possible to observe that the soil water restriction alters the growth and the final length of the one-year-old branches of peach tree. Water restrictions above 40% of water in relation to maximum transpiration cause precocious leaves fall of peach tree. The reference evapotranspiration calculated by the simplified Penman method presents slight relation with transpiration, evidencing its potentiality for the transpiration estimation of the peach tree. The water evaporation measured with a Piche evaporimeter is not appropriate for the estimation of the maximum transpiration of the peach tree. The soil water restriction above 20% of the maximum transpiration alters the fruits growth curve and reduces final size of the peaches fruits; however it does not alter the physico-chemical qualities. The water matric potential in the soil presents slight relation to leaf water potential, being used as an indicator of hydric stress in peach tree. The leaf water potential in peach tree considerably decreases from sunrise to noon showing an aniso-hydric model. The estomatic resistance and water potential on the leaf in peach trees at the sunrise or at noon are good indicators of hydric stress. Peach trees show a rapid recovery of its hydratation state in short periods of hydric deficit, supportting water restrictions up to 75% of water in relation to the maximum transpiration. (Support: FAPERGS)